Pemanfaatan Getaran Mesin Sebagai Sumber Energi Alternatif - Shivy Aura Adhyatma; Mohamad Hakam; Agus Khumaidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Energy cannot be created or destroyed. Transformation of energy is become one way to complete the renewable energy. In oftentimes machine vibrations is considered as interference, but the vibration energy can be convert into electrical energy. This research was conducted to design a machine vibration power plant that uses a mechanical system utilizing vibration energy from industrial machines. Ulrich method is used to determine the design concept. An energy conversion structure has been designed carrying the concept of a mechanical system, making eccentric motion using an intermediary plate system as a channel for engine vibration to cause up and down motion and supported by a transmission system into rotary motion to rotate a generator/dynamo as a generator of electricity. The vibrations generated from industrial machines can be utilized or converted into electrical energy. It is noted that the design of the energy conversion structure with a mechanical crankshaft system has not been able to convert vibrations into electricity according to the plan. The replacement of the material used in the crankshaft energy conversion structure is expected to improve the performance of the energy conversion tool. The engine vibration power plant is offered with a pump concept that can convert vibrations into electrical voltage. The result of the voltage is 0.035V and the resistance is 381.5 Ohms.